Severe Vitamin D Deficiency Is Associated With Increased Expression of Inflammatory Cytokines in Painful Diabetic Peripheral Neuropathy - Xiaohua, Gong; Dongdong, Luo; Xiaoting, Niu; Shuoping, Chen; Feixia, Shen; Huajun, Yang; Qi, Zhou; Zimiao, Chen (Frontiers in Nutrition, 2021)
Background: The exact pathogenic mechanism of the painful diabetic peripheral neuropathy (DPN) is poorly understood. Our study aimed to evaluate the association amongst vitamin D status, inflammatory cytokines and painful DPN. Methods: A total of 483 patients were divided into three groups, i.e. diabetes without DPN (no-DPN, n = 86), diabetes with painless DPN (painless DPN, n = 176) and diabetes with painful DPN (painful DPN, n = 221) groups. Basic information and laboratory results were collected. The concentrations of vitamin D (25-hydroxyvitamin D), high-sensitivity C-reactive protein, interleukin (IL)-2, IL-4, IL-6, IL-10, tumour necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) were also measured. Results: The prevalence of severe vitamin D deficiency (< 10 ng/mL) was more common in the painful DPN group than in the painless DPN and no-DPN groups (25.8%,12.5% and 8.1%, respectively, P<0.01). Cases in the painful DPN group had significantly higher concentrations of IL-6 (P < 0.01) and TNF-α (P < 0.01) than those in the two other groups. The multivariate logistic analysis showed that severe vitamin D deficiency, IL-6 and TNF-α were independent risks for painful DPN after adjusting for confounding factors. Furthermore, the vitamin D status had significantly negative correlations with IL-6 (r = −0.56, P < 0.01) and TNF-α (r = −0.47, P < 0.01) levels. Conclusion: Severe vitamin D deficiency was an independent risk factor for the painful DPN. Severe vitamin D deficiency status may play a role in the painful DPN pathogenesis through elevated IL-6 and TNF-α levels.